Co-elevation of atmospheric [CO2] and temperature alters photosynthetic capacity and instantaneous water use efficiency in rice cultivars in a cold-temperate region - Zhang, Chunyu; Li, Yansheng; Yu, Zhenhua; Wang, Guanghua; Liu, Xiaobing; Liu, Junjie; Liu, Judong; Zhang, Xingmei; Yin, Kuide; Jin, Jian (Frontiers in Plant Science, 2022)
Crop photosynthetic capacity in response to climate change likely constrains crop productivity and adaptability to changing environments, which requests the investigation on the dynamics of photosynthetic parameters over growth season among varieties, especially in cold-temperate regions. Three Japonica rice cultivars i.e., Shoubaimao (SH), Hejiang 19 (HJ); Longjing 31, (LJ). were planted under the control, e[CO2] (700 μmol mol-1), warming (2°C above the air temperature) and the co-elevation of [CO2] and temperature in open-top chambers (OTC). The objective of this study is to examine the rice photosynthetic parameters, water use efficiency (WUE) and yield formation in responses to the co-elevation of [CO2] and temperature which is the main predicted features of future climate. e[CO2] significantly increased An of SH, HJ and LJ by 37%, 39% and 23% in comparison to 34%, 34% and 27% under elevated [CO2] plus warming, respectively. However, An had a weak response to warming for three cultivars. [CO2] and temperature co-elevation significantly decreased the stomatal conductance, resulting in a significant increase of the WUE. e[CO2] significantly increased Vc, max, Jmax and Jmax/Vc, max. e[CO2] significantly increased grain yield and grain number of all cultivars. The positive effect of co-elevation of [CO2] and temperature on grain yield was less than e[CO2]. Warming is likely to partially offset the increased photosynthetic rate caused by e[CO2]. The [CO2] and temperature co-elevation may be favorable to rice crop with increasing the photosynthetic ability of rice crop and improving water use efficiency. The present study provided evidence that the rice genotypic difference in photosynthetic potential under [CO2] and temperature co-elevation. Therefore, it is crucial to explore a broader range of phenotypes and cultivars to be applied to climate change response research, advancing the knowledge that climate change impacts rice crop under the cold-temperate climate region.